Electrocatalytic Degradation of Phenol by the Electrooxidation-Electrocoagulation Hybrid Process: Kinetics and Identification of Degradation Intermediates - Ozturk, Hazal; Barisci, Sibel; Turkay, Ozge; Veli, Sevil (Asce-Amer Soc Civil Engineers, 2019)
The electrocatalytic degradation of phenol has been investigated by combining two processes, namely electrocoagulation (EC) and electrooxidation (EO), as a hybrid process. Ti/Pt-Fe and Ti/Pt-Al pairs of electrodes have been used in the study. The effects of various operating parameters such as electrode material, initial pH (pHi), applied current, and temperature have been evaluated based on phenol removal rate. Experimental results showed that the Ti/Pt-Fe electrode system provided more than 98% phenol removal for 3 h of process time at pHi 7.56 and applied current of 2 A. Kinetic studies were also conducted to understand the mechanism of the phenol removal by the hybrid process. The reaction kinetics for the EO part were fitted to a pseudo-first-order rate law, and the increase in kobs values was observed with the increase of applied current at pHi 7.56. For the adsorption part, diffusion was mostly the rate-controlling step for phenol uptake onto hydroxide flocs. The transformation by-products have been identified for the hybrid process, and it was seen that hydroquinone, benzoquinone, and pyrocatechol occurred at initial stages, and then benzoquinone and hydroquinone were subsequently converted to pyrocatechol. Through the final stages, the quinones converted to carboxylic acids, such as maleic acid and oxalic acid, because the phenol degradation and coagulation took place concurrently.
Keywords: Phenol; Electrocoagulation; Electrooxidation; Hybrid process; Kinetics; Degradation intermediates